GALERI SASIRANGAN DI BANJARBARU - Herlina, Yenny; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Sasirangan is a typical fabric of South Kalimantan that has a variety of types, motifs and techniques. Along with the development era Sasirangan experienced ups and downs of interest due to lack of public knowledge. Sasirangan Gallery is a form to promote sasirangan fabric, facilitating the process of buying and selling sasirangan fabric, providing knowledge to the public about the history, motifs and meaning of sasirangan fabric, and providing sasirangan wastewater treatment. Through the semiotic approach method with an interactive concept, users can understand the information provided by visual form and experience. This semiotic approach method is applied to emphasize the characteristics of Sasirangan motifs that are characteristic of Sasirangan fabrics. The Sasirangan Gallery design concept in Banjarbaru applies an interactive architecture in the building mass and space that refers to the material, texture and color in the space so that visitors can interact directly or indirectly.